Distribution and expression of esat-6 and cfp-10 in non-tuberculous mycobacteria isolated from lymph nodes of slaughtered cattle in Switzerland. (March 2019) - Scherrer, Simone; Landolt, Patricia; Friedel, Ute; Stephan, Roger
The most commonly used tools for tuberculosis testing in cattle, the tuberculin skin test and the interferon-γ release assay, detect immune reactivity to various antigens of Mycobacterium bovis, including ESAT-6 and CFP-10. However, some non-tuberculous mycobacteria (NTM) can also harbor the cfp-10 and/or esat-6 genes, which can lead to false-positive results. We tested 77 NTM isolates belonging to 22 different species from lymph nodes of healthy slaughtered cattle for the occurrence of cfp-10 and esat-6 . Most isolates did not harbor cfp-10 and esat-6 . However, M. gordonae, 'M. lymphaticum', M. kansasii, and M. persicum were cfp-10 positive. The esat-6 gene was found in M. kansasii and M. persicum. Protein expression of cfp-10 and esat-6 could be detected for M. kansasii and M. persicum. An effective tuberculosis control program based on interferon-γ release assays and tuberculin skin testing is dependent on further monitoring and characterization of NTM in a cattle population.